Efficacy of acupuncture for cocaine dependence: a systematic review & meta-analysis - Mills Edward J; Wu Ping; Gagnier Joel; Ebbert Jon O (BMC, 2005)
Background Acupuncture is a commonly used treatment option for the treatment of addictions such as alcohol, nicotine and drug dependence. We systematically reviewed and meta-analyzed the randomized controlled trials of acupuncture for the treatment of cocaine addiction. Methods Two reviewers independently searched 10 databases. Unpublished studies were sought using Clinicaltrials.gov, the UK National Research Register and contacting content experts. Eligible studies enrolled patients with the diagnosis of cocaine dependence of any duration or severity randomly allocated to either acupuncture or sham or other control. We excluded studies of acupuncture methods and trials enrolling patients with polysubstance use or dependence. We abstracted data on study methodology and outcomes. We pooled the studies providing biochemical confirmation of cocaine abstinence. Results Nine studies enrolling 1747 participants met inclusion criteria; 7 provided details for biochemical confirmation of cocaine abstinence. On average, trials lost 50% of enrolled participants (range 0-63%). The pooled odds ratio estimating the effect of acupuncture on cocaine abstinence at the last reported time-point was 0.76 (95% CI, 0.45 to 1.27, P = 0.30, I2 = 30%, Heterogeneity P = 0.19). Conclusion This systematic review and meta-analysis does not support the use of acupuncture for the treatment of cocaine dependence. However, most trials were hampered by large loss to follow up and the strength of the inference is consequently weakened.